Six foresight frames: Classifying policy foresight processes in foresight systems according to perceived unpredictability and pursued change - Minkkinen Matti; Auffermann Burkhard; Ahokas Ira (ELSEVIER SCIENCE INC, 2022)
Foresight is conducted in diverse ways drawing on particular sets of assumptions, and it increasingly takes place in networked foresight systems. We develop a typology of six foresight frames based on two dimensions: 1) level of perceived unpredictability and 2) level of pursued change. By frames, we mean the interpretive structures that underlie foresight actors' work. The six foresight frames are the predictive, planning, scenaric, visionary, critical and transformative frames. The frames may be used to position phases of foresight, individual processes or, most usefully, interlinked foresight processes in a system. We develop the model based on futures literature and elaborate it in a study of comprehensive security foresight in Finland conducted during the Strategic Research Council project "From Failand to Winland". Moreover, we test our typology with four additional foresight system cases: Singapore, United Kingdom, Wallonia and Russia. The six frames capture different sets of assumptions and different types of foresight which can be distributed to different actors in a foresight system. Thus we suggest that diversity of foresight frames is likely to be an element of successful foresight systems. However, this requires understanding the diversity of foresight frames and the competence to bridge different approaches.